Characteristics of undergraduate medical thesis of a Peruvian public university - Castro-Maldonado, Betty (2015)
The undergraduate thesis rather than a requirement to graduate, are a way of doing research. Previous studies show a thesis published between 2.7% to 17.6% in indexed journals. Objective: To describe the characteristics of the undergraduate thesis of a medical school. Material and Methods: Bibliometric study. 221 theses were reviewed, collecting: year, number of authors, advisers, and references, study population, and national priorities for health research. A search was performed on Google Scholar to assess publication. Descriptive statistics were used. Results: Of the total, 91.6% of thesis had one advisor, 76% were descriptive, 82.8% were done in a hospital population, 62.4% in adults. A lower production was found in the years 2008-2010.Of the theses between 2010-2014,72.9% did not correspond to any national health research priority. Only 6.8%was based on literature of the last five years. Only 9 (4.1%) were published in an indexed scientific journal. Conclusion: The undergraduate thesis were characterized as descriptive, in hospitals, in adults, based on out dated literature and not in line with the national priorities for health research. The publication is low.